The Regulation of Leptin, Leptin Receptor and Pro-opiomelanocortin Expression by N-3 PUFAs in Diet-Induced Obese Mice Is Not Related to the Methylation of Their Promoters - Qi Kemin (Nutrition & Metabolism, 2011)
Abstract Background The expression of leptin is increased in obesity and inhibited by n-3 polyunsaturated fatty acids (n-3 PUFAs), but the underlying molecular mechanisms have not been firmly established. Methods In this study, we investigated the effects of dietary n-3 PUFAs on the methylation of CpG islands in the promoter regions of the leptin, leptin-R and POMC genes, as well as the effects of n-3 PUFA status in early life on the modification of the promoters of these three genes. Male C57 BL/6J mice were fed a high-fat diet with one of four different fat types: sunflower oil (n-3 PUFA deficient), soy oil, fish oil, or a mixture of soy and fish oil (soy:fish oil = 1:1). Two low-fat diets with sunflower oil or soy oil served as controls. Female mice were fed two breeding diets, sunflower oil or a mixture of soy and fish oil (soy:fish oil = 1:1), during pregnancy and lactation to breed new pups. Results Compared to mice fed the control diets, the expression of leptin in fat tissue and leptin-R and POMC in the hypothalamus was higher in the diet-induced obesity (DIO) mice, and the n-3 PUFAs in the diets reversed these elevated expression levels. The mean methylation levels of CpG sites in the promoter regions of the leptin and POMC genes showed no difference between the DIO and the control diet groups nor between the n-3 PUFA-containing and -deficient diet groups. For the CpG sites in the promoter regions of leptin-R, no methylation was found in any of the DIO or control groups. Feeding mice with the n-3 PUFA diet during pregnancy and lactation did not affect CpG methylation in the leptin or POMC promoters. Conclusions Our findings indicate that promoter DNA methylation may not be related to the expression of leptin, leptin-R or its related hypothalamic satiety regulator POMC.